(untitled) (Bangladesh Journal of Zoology, 2012)
Toxicological properties of the indigeneous plant Achras zapota (Linn) (Family: Sapotaceae) (locally known as ’Safeda’ in Bangla) were assessed on two predatory fishes, Heteropneustes fossilis (Bloch) and Channa punctatus (Bloch), after 24 h exposure under normal laboratory conditions (25 ± 3ºC). Distilled water, 50% and absolute ethyl alcohol solvent extrarcts of the dry seed, leaf, bark and root of A. zapota were tested upon the fishes. Exposed fishes showed hyperactivity with increased opercular movement and accumulation of mucus on the body surface. Increase in the concentration of the extracts caused an increase in the fish mortality. The LC50 values of the distilled water, 50% ethyl alcohol and absolute ethyl alcohol extracts of A. zapota plant parts for H. fossilis were 320.80, 222.26, 98.49 ppms, respectively in seed; 480.91, 279.37, 235.76 ppms, respectively in leaf; 630.86, 151.39, 85.21 ppms, respectively in bark and 218.12, 122.89, 111.62 ppms, respectively in root. Whereas, the LC50 values of the corresponding plant parts for C. punctatus were 218.12, 146.84, 88.83 ppms, respectively in seed; 279.35, 175.89, 125.69 ppms, respectively in leaf; 132.36, 102.91, 78.11 ppms, respectively in bark and 63.87, 39.46, 33.27 ppms, respectively in root. On the basis of the LC50 values of absolute ethyl alcohol extracts, for H. fossilis, the order of toxicity was found to be: bark > seed > root > leaf and for C. punctatus it was: root > bark > seed > leaf. Of the two test fishes H. fossilis was more tolerant and less sensitive to the effects of the plant part extracts than C. punctatus. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12900 Bangladesh J. Zool. 40(1): 109-119, 2012